Experimental and theoretical investigation of the room-temperature photoluminescence of amorphized Pb(ZrTi)O-3 - Orhan, E.; Pontes, F. M.; Leite, E. R.; Pizani, P. S.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Wiley-Blackwell, 2005)
Ultrafine PbZr0.20Ti0.80O3 was omorphized through high-energy mechanical milling. The structural evolution through the omorphization process was accompanied by various characterization techniques, such as X-ray diffraction, Fourier-transformed IR spectroscopy (FTIR), high-resolution transmission electron microscopy (HR-TEM), and Raman spectroscopy. A strong photoluminescence was measured at room temperature for amorphized PbZr0.20Ti0.80O3, and interpreted by means of high-level quantum mechanical calculations in the density functional theory frame-work. Three periodic models were used to represent the crystalline and amorphized PbZr0.20Ti0.80O3, and they allowed the calculation of electronic properties that are consistent with the experimental data and that explain the appearance of photoluminescence.
Keywords: amorphization; density functional calculations; metal oxides; photoluminescence; X-ray diffraction